The role of global open data infrastructure in a changing policy, technology, and research environment - Lippincott, Sarah; Treadway, Jon (Septentrio Conference Series, 2023)
Watch VIDEO. The proliferation of open data sharing policies (such as the wide-reaching NIH policy and Nelson Memo in the United States) reflect a growing push for greater collaboration, transparency, and accountability in scientific research. They assert that the open sharing of data underpinning research is essential to achieving the benefits of open science, that researchers and the general public have a right to access that data, and that the value of shared data lies in its (re)usability. As the scientific community rallies to meet these new requirements, research data infrastructures like Dryad, an open data publishing platform and community, face myriad opportunities and challenges. In this talk, the presenters will summarize the impact that new policies, evolving researcher and institutional needs, coordinated support for open infrastructure, and other changes in the landscape are having on the Open Data movement and those that support it; provide insight into Dryad’s experience addressing challenges like increasing file size and complexity, and simplifying data deposition workflows; explore the opportunities and challenges presented by emerging new technologies such as machine learning, automation, and distributed data storage; outline the ongoing relevance of non-specialist data infrastructures in the rapidly evolving research landscape, and how their role will have to change through collaboration and partnerships.